PEMBUATAN APLIKASI PEMBELAJARAN AKOR DASAR GITAR - Lalela, Julius Saint Michael; Rokhayati, Yeni (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2020)
Every person is now easier to express themselves through music. Many music-themed applications can be found on smartphones, including those based on Android. With the rapid development of smartphone technology nowadays, more and more applications are used as learning media. With the rapid development of technology, an application that can help a beginner guitarist learn basic guitar chords, their shape and tone, is needed. Therefore, an application was developed to facilitate beginner guitarists to learn basic guitar chords. In making this application, the software used consisted of Adobe Flash CS5, Adobe Air, Android Emulator, Android SDK, Adobe Photoshop CS6, and Sound Recorder application. This application had been tested and successfully implemented to facilitate beginner guitarists to learn basic guitar chords, along with their shape and tone.